The Influence of Facility Provision, Product Diversity and Product Quality on the Decision to Purchase Fruit Products at the Cibitung Main Market - Kamal, Wafiq Fadlul; Untari, Dhian Tyas; Andrian, Andrian (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of facility provision, product diversity and product quality on consumer purchasing decisions for fruit products at the Cibitung Main Market. This research is quantitative research that uses primary data through questionnaires distributed directly to each consumer of the Cibitung Main Market. The number of questionnaires distributed was 98 with the research subjects being business people who spent their fruit product needs at the Cibitung Main Market. Based on the results of statistical tests, it proves that facilities influence purchasing choices. However, the product diversity variable has a significance value of 0.302, which is greater than 0.05. As a result, hypothesis H2 was rejected, which means there is no significant relationship between product diversity and purchasing decisions.